2015
DOI: 10.1111/ijd.12679
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of latent tuberculosis infection in patients with moderate to severe psoriasis taking biologic therapies in a dermatologic private practice in Miami, Florida

Abstract: The use of a screening tool for LTBI is mandatory in patients taking biologic therapies to avoid severe infectious complications. Periodic follow-up is also crucial as positive results may be seen after prolonged use of these agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 21 publications
(54 reference statements)
0
16
0
Order By: Relevance
“…The aim of the screening before the treatment start and during the follow‐up is to detect a possible quiescent state of the Mycobacterium tuberculosis infection called latent tuberculosis infection (LTBI) 1 . Opportunistic infections reactivation, especially LTBI, is one of the main risks during biologic therapy, in particular with TNF‐α inhibitors 2‐4 . TNF‐α, an inflammatory cytokine that plays a central role in the pathogenesis of psoriasis, is also involved in the control of bacterial infections and granuloma formation to limit pathogens dissemination.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The aim of the screening before the treatment start and during the follow‐up is to detect a possible quiescent state of the Mycobacterium tuberculosis infection called latent tuberculosis infection (LTBI) 1 . Opportunistic infections reactivation, especially LTBI, is one of the main risks during biologic therapy, in particular with TNF‐α inhibitors 2‐4 . TNF‐α, an inflammatory cytokine that plays a central role in the pathogenesis of psoriasis, is also involved in the control of bacterial infections and granuloma formation to limit pathogens dissemination.…”
Section: Introductionmentioning
confidence: 99%
“…Also, IL‐12 and IL‐23 play an important role in the immunologic barrier against bacterial or parasitic infections 5 . For these reason, TB screening and eventual TB infection prophylaxis in case of screening positivity for LTBI are mandatory before starting a biologic treatment 2,3 . Among TNF‐α inhibitors, etanercept (a soluble TNF‐α receptor) is associated with a lower risk of reactivation than infliximab and adalimumab (monoclonal antibodies) because of a probable reduced interference with granuloma formation and higher clearance rate 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 In a study conducted in the USA where patients with psoriasis were evaluated before the biological drug treatment, the rate of latent tuberculosis was examined by the tuberculin test and found to be positive in about 4.5% of the cases. 15 In a study in Italy this rate was found to be 8.2%. 14 In this study, latent tuberculosis infection was diagnosed in the clinic for chest diseases by clinical evaluation, ppd / quantiferon test and chest x-ray.…”
Section: Discussionmentioning
confidence: 92%
“…Studies report a highly heterogeneous TST positivity rate in patients with psoriasis, ranging between 4.5% and 99% (7,8). The present study was conducted in Israel, where the tuberculosis burden is low (4:100,000) (6).…”
Section: Discussionmentioning
confidence: 94%